Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae - Roy, Sukhendu; Hazra, Niladri (Zootaxa, 2016)
A new species of the genus Viridopromontorius Luna de Carvalho is described from West Bengal, India. The new species V. aequus differs from the other member of Viridopromontorius by having approximately equal size of antennomeres IV and V, maxillary palp nearly twice the length of base, vein R4 curved towards R2, very small distal process on tarsomeres II–III, tarsomere IV almost trapezoidal and acumen to some extent upwardly bent (in lateral view). A revised key of the family Corioxenidae is also provided.